Fundamentos da garantia constitucional do duplo grau de jurisdição - Marina França Santos (2011)
The goal of this study is to investigate what is the position occupied by the right to appeal in the contemporary civil legal procedure. It starts with the discovery of a widespread discourse, which has repercussions in the production of law, that the systematic of the right to appeal represents, today, an inconvenient remnant of the history of law and an impediment to celerity and effective process. To verify the veracity of this premise, it was sought to develop, initially, a compendium of the teleological evolution of civil procedure, in order to outline both its normative and axiological frame in the legal system, and the proper value of celerity in this scenario. Then, we tried to conceive the reasons, justifications and criticisms addressed by the literature, national and foreign, of the right to appeal. The effectiveness of the procedure, examined mainly in the works of Barbosa Moreira, constitutes the research theoretical framework, which is guided, also, by a garantism and constitutional model of process, supported, among all the valuable contributions, by the works of Ítalo Andolina, Luigi Ferrajoli and Serio Galeotti. The hypothesis worked is that the two levels of jurisdiction, despite its functions as one recognized factor in the time extension of the procedure, configures, given the contemporary imperatives of effective legal procedure, fundamental constitutional guarantee, and as such, must be preserved by the Brazilian law . It is intended, after all, to offer a study that serves as a warning to the legal community to the risk of sponsoring reforms that, hiding the values of the Rule of Law, advocate an immediate solution to celerity problems, with a corresponding weakening of civilizational achievements widely implemented by constitutional guarantees of procedure.